2016
DOI: 10.1080/19448953.2016.1196019
|View full text |Cite
|
Sign up to set email alerts
|

Turkey as ‘a positive other’: a theoretical discussion to comprehend the British media’s view on Turkey–EU relations

Abstract: No country has waited at the front door of the EU as long as Turkey yet. In addition to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
(5 reference statements)
0
3
0
Order By: Relevance
“…According to the literature, the British media took either a positive or a negative approach towards Turkey. They perceived and made this country get perceived as "the other" (Schneeberger, 2009;Arcan, 2012;Bora, 2015;Paksoy & Negrine, 2016). However Turkey was serving as a "model" for the Islamic world.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the literature, the British media took either a positive or a negative approach towards Turkey. They perceived and made this country get perceived as "the other" (Schneeberger, 2009;Arcan, 2012;Bora, 2015;Paksoy & Negrine, 2016). However Turkey was serving as a "model" for the Islamic world.…”
Section: Discussionmentioning
confidence: 99%
“…Yet another study was more extensive than those discussed above; it focused on The Guardian, The Daily Telegraph, the Financial Times, the Daily Mail, the Daily Mirror, and the BBC News Online (Paksoy & Negrine, 2016). This study reported the findings from a content analysis of the news between 1999 and 2006, when Turkey's bid for EU membership was a hot topic.…”
Section: Previous Researchmentioning
confidence: 99%
“…Finally, Paksoy and Negrine (2016: 500) emphasize that Turkey is represented as a ‘positive other’ in British media. Turkey is not only depicted as ‘other’ in conventional terms, but also considered to have a potential to function as a bridge betwen the East and the West assisting Europe to reach out to the Muslim world (Ibid).…”
Section: The Fourth Period (1999–2016)mentioning
confidence: 98%